Gun Violence and Psychopathy Among Female Offenders - Thomson, Nicholas D. (Frontiers in Psychology, 2022)
Research exploring risk factors of gun violence is limited, especially research involving women as perpetrators of violence. Yet, women account for 18–21% of convicted violent crime. The present study aimed to test if psychopathy, a notable risk factor for violence, was related to past convictions of gun violence, general forms of violence, and non-violent crime. In a sample of 206 female offenders, multinomial logistic regressions assessed how interpersonal, affective, and behavioral psychopathic traits increased the likelihood of women belonging to the gun violence group, a violent crime group, and a non-violent crime group. Results showed the interpersonal and affective facets increased the likelihood of women belonging to the gun violence group compared to both the violent and non-violent crime groups. The behavioral facet increased the likelihood of women belonging to the violent crime group when compared to the gun violence and non-violent crime groups. These results suggest that gun violence has different risk factors than violent and non-violent crime. This line of inquiry indicates that existing violence prevention strategies may need to be modified to address gun violence.